Vietnam : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
In this study, the following are listed in detail: gross domestic product by expenditure and by sector and ownership at current prices and at constant prices, consumer price inflation, gross value of agricultural production at constant prices, production of food staples, industrial crop production by sector ownership at constant prices, population and employment, summary of general government budgetary, revenues and expenditures, monetary survey, distribution of credit, balance of payments, merchandise export and import by commodity, summary of normal tariff schedule, and tax system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet